The effect of Marketing Strategy, Service Quality, and Consumer Psychology Aspects of Mypertamina Application Users on Sales Volume in 2024 in an Islamic Business Perspective (Study on Gas Station Consumers in Bandar Lampung) - Nazira, Aliya; Habibi, Ahmad; Susanti, Yeni (Journal of Economics and Social Sciences (JESS), 2025)
This study analyzes the influence of marketing strategies, service quality, and aspects of Consumer Psychology on the sales volume of the MyPertamina application in Bandar Lampung in the perspective of Islamic Business. Quantitative methods with survey techniques were used on 100 respondents of active users of MyPertamina at Bandar Lampung gas station. The Data were analyzed using multiple linear regression with SPSS 26.0 software. The results showed that the three variables have a positive and significant effect on sales volume, with aspects of Consumer Psychology has a dominant influence (β=0.467), followed by marketing strategy (β=0.423) and quality of Service (β=0.381). Simultaneously, the three variables explained 67.7% variation in sales volume (R2=0.677). From the perspective of Islamic business, the practice of MyPertamina demonstrates conformity to the principles of justice, transparency, and mutual blessing, although aspects of security and social norms need improvement. The research provides a strategic blueprint for optimizing customer psychology management and integration of Islamic features in the energi digital platform.